2012
DOI: 10.2139/ssrn.2073475
|View full text |Cite
|
Sign up to set email alerts
|

Early Phase Success and Long Run Failure of Economic Sanctions: With an Application to Iran

Abstract: We develop a model of the dynamics of economic sanctions in conjunction with the response of the sanction target. We apply this model to the case of the EU and US boycott of Iranian oil. Our VAR model finds significant impacts of sanctions both on key economic variables and on the political system. These effects, however, are limited in time and occur in the first two to four years of the sanction episode only because adjustment of economic structures mitigates the economic and political impact of the sanction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…On the other hand, import transaction costs and then imported goods inflation rises that cause a decline in household imported consumption and investment following Eyler (2007) and Gagnon and Ihrig (2004). A decline in domestic production, nonoil exports and oil production results in decreasing GDP and unemployment with an increasing inflation rate and altogether a condition of stagflation that is consistent with Rahmati et al (2016) and Dizaji and van Bergeijk (2012). CBI's priority is controlling the inflation rate as it causes a decline in monetary base growth.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 70%
See 1 more Smart Citation
“…On the other hand, import transaction costs and then imported goods inflation rises that cause a decline in household imported consumption and investment following Eyler (2007) and Gagnon and Ihrig (2004). A decline in domestic production, nonoil exports and oil production results in decreasing GDP and unemployment with an increasing inflation rate and altogether a condition of stagflation that is consistent with Rahmati et al (2016) and Dizaji and van Bergeijk (2012). CBI's priority is controlling the inflation rate as it causes a decline in monetary base growth.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 70%
“…Farzanegan et al (2016) studied the effects of oil sanctions using computable general equilibrium (CGE) model based on social accounting matrix (Sam) table of Iran in 2001 which showed that oil sanctions brought about a GDP decline and a decline in trade, consumption and CPI and increased the exchange rate. Dizaji and van Bergeijk (2012) studied the effects of oil shock in the US and EU from 1965 to 2008 using vector autoregressive (VAR). The results showed that declining oil revenue changes Iran's political behavior toward democracy and leaves negative effects on the macroeconomic variables such as consumer price index, real exchange rate, real investment and real national product in the short run that disappears because of economic reforms in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we also 5 Data on real oil and gas rents and defence expenditures are the limiting factors. Note that Dizaji & van Bergeijk (2012) …”
Section: Choice and Sequence Of Variablesmentioning
confidence: 99%
“…Sajjad Faraji Dizaji and Peter A.G. van Bergeijk conducted a study of changes in the impact of sanctions over time and came to the conclusion that for the imposed sanctions only the first few years are critical, and in the fourth or fifth year the country's economy is already adjusting to the sanctions and continues further development [8].…”
Section: Financial Sanctions and Investment Attractiveness Of Thementioning
confidence: 99%